Girls to the rescue, book #2 : tales of clever, courageous girls from around the world - Lansky, Bruce (Deephaven, MN : Meadowbrook Press ; New York : Book Trade Distribution by Simon & Schuster, 1995)
A collection of ten stories, with author biographies, featuring admirable girls in both familiar and exotic settings.
Cody's wooden whistle -- Adrianna's chickens -- Liza and the lost letter -- Jamila and the tiger -- The peacemakers -- Kim's surprise witness -- Vassilisa the wise -- Just a girl -- The clever daughter-in-law -- Peggy's magic egg.
710
Keywords: Children's stories; Short stories